2021
DOI: 10.1111/eje.12669
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum setting and students' feedback of pre‐clinical training in different dental schools in China—A national‐wide survey

Abstract: Introduction Adequate time and effective training facilities are essential for undergraduate dental students participating in pre‐clinical dental practice to ensure them providing safe treatment for patients in the future. The study aimed to explore the current status of pre‐clinical dental training in China in relation to the curriculum setting and students' feedback of pre‐clinical training in different dental schools and thus provide information for further standardise curricula. Materials and method An onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Due to the lack of vision, it is di cult for medical students to see the extraction process of the inner most retaining teeth in the mouth during clinical teaching. Moreover, with the increasing awareness of patient self-protection, more patients want to be treated by more experienced doctors and refuse to be treated by medical students, which reduces the opportunity of clinical practice for medical students [6,7] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of vision, it is di cult for medical students to see the extraction process of the inner most retaining teeth in the mouth during clinical teaching. Moreover, with the increasing awareness of patient self-protection, more patients want to be treated by more experienced doctors and refuse to be treated by medical students, which reduces the opportunity of clinical practice for medical students [6,7] .…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide survey on curriculum design and students’ feedback in Chinese dental schools showed that the allocated time for periodontology courses was insufficient. 6 Traditional jaw models, commonly used for dental skill training, have several limitations including the absence of timely feedback, difficulties in presenting complex 3-dimensional geometry clearly, and distorted haptic perception of plastic gingiva and teeth. Therefore, it is imperative to explore new, effective teaching methods for subgingival scaling.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many dental schools lack such specialized training on ultrasonic scaling [ 12 ]. The reasons include limited teaching time, the current curricula outline setting focused on manual instruments, the relative shortage of effective laboratory resources, and the infeasibility of repeated intrusive training on patients [ 13 ]. To address these deficiencies, some dental schools have introduced several traditional materials, such as quail eggs, pop-top cans, and bionic models of extracted teeth, into pre-clinical periodontal education [ 14 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual simulation (VS) technology may be a real boon in such training [ 13 , 18 – 20 ]. With multi-sensory feedback capabilities, VS can create highly realistic specialized scaling environment, provide real-time standardized assessment, and offer repeatable practicing opportunities for students.…”
Section: Introductionmentioning
confidence: 99%